The advancement of technology in the labor market: a re-reading of the fundamental right to protection against automation - FABRIZ, Daury; MARTINELLI, Claudio (Utopía y Praxis Latinoamericana, 2025)
Technology has progressively replaced human labor, making protection against automation essential, as established in Article 7, Section XXVII of the 1988 Federal Constitution. Automation impacts both manual and intellectual work, requiring measures to ensure decent employment. Given this, the question arises: how can workers be protected against technological advancements? To address this, this article explores: (i) artificial intelligence; (ii) impacts on contemporary sociology; (iii) the future of the labor market; and (iv) the fundamental right to protection against automation. It is concluded that unregulated automation threatens fundamental rights, demanding an adequate legal framework, professional training for market adaptation, and public policies that strengthen labor income, ensuring social justice.